PENGARUH PENGALAMAN AUDITOR, PREFERENSI KLIEN, DAN TIMELINESS TERHADAP KUALITAS AUDIT DENGAN ETIKA AUDITOR SEBAGAI VARIABEL MODERASI (SURVEY PADA KANTOR AKUNTAN PUBLIK DI JAKARTA SELATAN) - Cheow William; Sukrisno Agoes; Henny (Fakultas Ekonomi Universitas Tarumanagara, 2023)
The purpose of research this study was to know the influence of auditor experience, preference of the client and timeliness for audit quality. In this research the survey was conducted with responden is an auditor who works in the public accountant firm (KAP), which domicile in South of Jakarta. The survey technic in this research is sending questionnaire to responden then questionnaire will be filled. Independence variable is auditor experience, preference of the client and timeliness and dependend variable is audit quality and moderate variable is ethical of auditor. Based on the analysis and testing shows that, the experience of the auditor, client preferences and timeliness variable has a significantly affect the audit quality in the public accountant firm in South of Jakarta and also ethical of auditor was moderate independent and dependent variable.